Scientometric Analysis of Indian Citation Index (2004-2015): Profile of the Domain of Energy and Fuel Science Journals - G., Ulaganathan; Senthilkumar, R (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 3 No 1&2 (2016): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
Indian Citation Index database is a powerful tool to search, track, and measure and collaborate in the sciences, social sciences, arts, and humanities. This article discusses the published research articles, citations and self-citations in the Energy and Fuel Science Journals which are available in Indian Citation Index. There are 7 9 3 articles published from 5 Energy and Fuel Science Journals. Among them, Journal of Mines, Metals and Fuels occupies first position with 442 (55.74%) articles and Journal of Energy Heat and Mass Transfer occupies second rank with 140 (17.66%) articles and Journal of Biofuels is in third 79 (9.96%). It is pointed out that the frequency of the journals is varying and that is one of the reasons for the strength of articles. Further, in the year 2010, 98 (12.36%) articles are published and it is highest when comparing to other years.